(untitled) (Philological Studies, 2019)
The article deals with the prose of contemporary female writers from the Koroška region, i.e., with a detailed insight into the respective artists’ choice of theme, produced work, and creative process. Contemporary female writers from the Koroška region – Silvija Borovnik, Cvetka Bevc and Barbara Simoniti – write high quality literary works. Their writings differ in genre and style. This article with the focus on analyzing said works, by incorporating the theoretical findings of Ingrid and Horst Daemmrich, particularly in regards to theme and process. The second part takes into consideration those literary works or short stories of contemporary female writers from the Koroška region in which motifs are an integral part of the literary work: the novels Soba gospe Bernarde (2007), Ina (2011) and Potovci (2011), and short-story collection Zgodbe iz somraka, 2007), all by Cvetka Bevc; the short-story collection Strašljivke (1990) by Sivija Borovnik; and the short-story collection Razdalje (1998) by Barbara Simoniti.